Community-acquired and healthcare-associated Staphylococcus aureus infections in a pediatric hospital in southern Brazil over 8 years: how common is MRSA? - Fassbind, Derrick Alexandre; Rezende, Raíssa Queiroz; Dias, Cícero Armídio Gomes; Motta, Fabrizio (Frontiers in Pediatrics, 2023)
Backgrounds: Both healthcare-associated and community-acquired methicillin-resistant Staphylococcus aureus (MRSA) infections are relevant in children. The objective of our study was to evaluate their impact in a pediatric hospital in southern Brazil. Methods: Data from patients under 18 years of age with S. aureus infections between January 2013 and December 2020 were retrospectively analyzed. Data were collected regarding infection site, infection type (community-acquired or healthcare-associated), susceptibility to oxacillin (methicillin-susceptible S. aureus [MSSA] or MRSA) and other antimicrobials. We analyzed the evolution of the susceptibility rates for the isolates over this period. Results: A total of 563 patients were included, among whom the prevalences of community- and hospital-acquired MRSA infections were 46.1% and 8.1%, respectively. No significant change occurred in these prevalences over the study period. In community-acquired infections, MSSA was significantly more associated with osteoarticular infections and MRSA was more associated with respiratory and intra-abdominal infections. In healthcare-associated infections, there was an association between MSSA and primary bloodstream infections and between MRSA, skin/soft tissue infections, and respiratory infections. Community-acquired MRSA were highly susceptible to trimethoprim-sulfamethoxazole (96.1%), clindamycin (88.4%), and doxycycline (99.0%). Conclusion: Our study draws attention to the high rates of MRSA in community-acquired staphylococcal infections in this population, indicating a need to review initial protocols for severe staphylococcal infections according to local epidemiology.